Comparative analysis of myocardium repolarization abnormalities in female biathlon athletes with different fitness levels - Bolotin, A.; Bakayev, V.; You, C. (Journal of Human Sport & Exercise, 2018)
The problem of studying the heart rate regulation is the most important in the assessment of functional readiness of female athletes to competitive activity. It was found that the main indicator of the fitness degree of the female biathlon athletes is clear consistency between the nervous and hormonal components of the heart rate regulation. Harmonization of both components of the heart rate regulation indicates high adaptive possibilities of the female athletes` organism to the loads. The heart rate regulation was studied with the help of the three-channelled electrocardiograph "Axion". "Varikard 2.51" was used to study the cardiointervalograms. It was established that myocardial repolarization abnormality in female athletes leads to misalignment between the two components of heart rate regulation and, as a consequence, to overtraining. It was revealed that the expressed misalignment between two components of heart rate regulation testifies to poor tolerance of physical loading by sportswomen. It was established that with the help of assessment of myocardium repolarization abnormalities in female athletes it is possible to estimate their functional reserves and effectively manage the training process, as well as to predict excessive physical loads at the early stages.